Catalyst for deep hydrodenitrogenation and desulfurization and preparation method thereof
By using pseudo-thin aluminite and oxidized metals as support and active components in the hydronitrition desulfurization catalyst, and adopting a specific preparation process, the problem of easy coking of the catalyst is solved, the catalyst's anti-coking performance and denitrification desulfurization ability are improved, and the service life is extended and the cost is reduced.
Patent Information
- Application Number
- CN202411845436.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
AI Technical Summary
Existing hydronitrition desulfurization catalysts are prone to coking due to high activity, reducing reaction activity and increasing reactor pressure, affecting production efficiency and equipment safety.
A catalyst support with high specific surface area and suitable pore volume is prepared by using pseudo-thin aluminite as a support, combining molybdenum oxide, nickel oxide and silicon oxide as active components, and a catalyst support with a high specific surface area and suitable pore volume is prepared through a specific mixing and drying process. The anti-coking performance of the catalyst is further improved through the fixation and secondary impregnation treatment of the impregnation liquid.
It significantly improves the ability of hydronitrition and hydronitrition, extends the service life of the catalyst, reduces production costs, and increases the profit margin of the product.
Smart Images

Figure BDA0005189059960000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a deep hydrodenitrogenation and desulfurization catalyst and a preparation method thereof. Background Art
[0002] Hydrodenitrogenation and desulfurization catalysts are essential catalyst products for petroleum-based and coal tar-based hydrogenation technologies. The performance of hydrodenitrogenation and desulfurization catalysts directly affects the properties of the products produced by the hydrogenation reactor. The ability of hydrodesulfurization and denitrification also directly affects the profit margin of product output. The catalyst is mainly composed of active metals and carriers. Usually, the products of hydrodenitrogenation and desulfurization catalysts need to have high activity and high anti-coking ability. These two properties are exactly conflicting. Highly active hydrodenitrogenation and desulfurization catalysts often make the reaction raw materials polymerize quickly to produce coking, which blocks the reaction channels after coking, reduces the reaction activity, increases the pressure drop of the reactor, brings pressure to the production process, and has the risk of damaging the reactor. Summary of the invention
[0003] In view of the problems existing in the background technology, the present invention provides a catalyst for deep hydrodenitrogenation and desulfurization and a preparation method thereof. The catalyst obtained by the method not only solves the problem of easy coking, but also greatly improves the ability of hydrodenitrogenation and hydrodesulfurization.
[0004] The above purpose is achieved through the following technical solutions:
[0005] The raw material used is pseudo-boehmite product, and the active components include molybdenum oxide, nickel oxide and silicon oxide.
[0006] Preferably, the active component molybdenum oxide in the catalyst is 18-25%.
[0007] Preferably, the active component nickel oxide in the catalyst is 3.3-5.5%.
[0008] Preferably, the active component silicon oxide in the catalyst is 1-3%.
[0009] Preferably, the catalyst product has a specific surface area of 130 to 170 m 2 / g, pore volume 0.3~0.5ml / g, pore diameter 7~12nm.
[0010] Preferably, the pseudo-boehmite raw material has a specific surface area of 280 to 350 m 2 / g, and the pore volume is 0.8~1.2ml / g.
[0011] More preferably, the raw material pseudo-boehmite is added with anti-coking factor silicon element, the content of which is 2% to 4%.
[0012] Preferably, in step 1, pseudo-boehmite, sesbania powder and hydroxymethyl cellulose are placed in a kneader and stirred for 10 to 30 minutes. Then, deionized water and inorganic acid are taken to prepare a solution, the pH value is adjusted to 2 to 4, the prepared solution is added to the kneader, kneaded until the product is a mass material, and the amount of water added is adjusted to the appropriate dryness and wetness of the product.
[0013] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0014] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 50-100°C for 4 hours under a nitrogen atmosphere, and then heat it to 500-650°C at a rate of 3°C / min and calcine it at a constant temperature for 4-8 hours to obtain the catalyst carrier.
[0015] Step 4: Add deionized water to the soluble molybdenum salt and nickel salt to fully dissolve them to prepare a stable impregnation solution.
[0016] Step 5: Mix the prepared impregnation liquid with the catalyst carrier obtained above in a fixed ratio and impregnate for 2 hours, then dry it at 50-100°C for 4 hours in a nitrogen atmosphere, then perform a second impregnation of equal volume for 1 hour, dry it at 75-120°C for 2 hours in a nitrogen atmosphere, and then heat it to 300-500°C at a rate of 3°C / min and calcine it at a constant temperature for 4 hours to obtain the catalyst product.
[0017] The deep hydrodenitrogenation and desulfurization catalyst and preparation method thereof provided by the present invention have the following advantages:
[0018] (1) The raw materials used in catalyst production are redesigned, which reduces the production process of the hydrodenitrogenation and desulfurization catalyst, reduces production costs, and improves product profit margins.
[0019] (2) The hydrodenitrogenation and desulfurization catalyst has greatly improved the hydrodenitrogenation and hydrodesulfurization capabilities due to the replacement of production materials and production methods, thus solving the problem that ordinary hydrodenitrification catalysts cannot achieve deep denitrification and desulfurization.
[0020] (3) The hydrodenitrogenation and desulfurization catalyst has an anti-coking factor added to the raw material stage, thereby solving the problem of easy coking due to high activity during use, thereby improving the service life of the catalyst. DETAILED DESCRIPTION
[0021] The following embodiments of the technical solution of the present invention are described in detail in conjunction with the embodiments. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and cannot be used to limit the protection scope of the present invention.
[0022] It should be noted that the experimental methods used in the implementation examples are all conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be obtained from commercial channels.
[0023] Example 1
[0024] Step 1: first, place 600g of pseudo-boehmite, 24g of sesbania powder, and 36g of hydroxymethyl cellulose in a kneader and stir and mix for 10 minutes. Take 270ml of deionized water and 270ml of nitric acid to prepare a solution, adjust the pH value to 3, then add the prepared solution to the kneader, knead until the product is a lump-like material, and adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0025] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0026] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 50°C for 4 hours under a nitrogen atmosphere, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 6 hours to obtain the catalyst carrier.
[0027] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0028] Step 5, the prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, followed by a second impregnation of equal volume for 1 hour, dried at 75°C under a nitrogen atmosphere for 2 hours, and then heated to 300°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain product 1.
[0029] Example 2
[0030] Step 1: first, place 600g of pseudo-boehmite, 24g of sesbania powder, and 36g of hydroxymethyl cellulose in a kneader and stir and mix for 10 minutes. Take 270ml of deionized water and 270ml of nitric acid to prepare a solution, adjust the pH value to 2, then add the prepared solution to the kneader, knead until the product is a lump-like material, and adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0031] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0032] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 100°C for 4 hours under a nitrogen atmosphere, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 4 hours to obtain the catalyst carrier.
[0033] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0034] Step 5, the prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 100°C for 4 hours, followed by a second impregnation of an equal volume for 1 hour, dried at 100°C for 2 hours under a nitrogen atmosphere, and then heated to 400°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain product 2.
[0035] Example 3
[0036] Step 1: first, place 600g of pseudo-boehmite, 24g of sesbania powder, and 36g of hydroxymethyl cellulose in a kneader and stir and mix for 10 minutes. Take 270ml of deionized water and 270ml of nitric acid to prepare a solution, adjust the pH value to 4, then add the prepared solution to the kneader, knead until the product is a lump-like material, and adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0037] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0038] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 50°C for 4 hours under a nitrogen atmosphere, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 4 hours to obtain the catalyst carrier.
[0039] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0040] Step five, the prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, followed by a second impregnation of equal volume for 1 hour, dried at 75°C under a nitrogen atmosphere for 2 hours, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain product 3.
[0041] Example 4
[0042] Step 1: first, place 600g of pseudo-boehmite, 24g of sesbania powder, and 36g of hydroxymethyl cellulose in a kneader and stir and mix for 10 minutes. Take 270ml of deionized water and 270ml of nitric acid to prepare a solution, adjust the pH value to 3, then add the prepared solution to the kneader, knead until the product is a lump-like material, and adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0043] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0044] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 50°C for 4 hours under a nitrogen atmosphere, and then heat it to 650°C at a rate of 3°C / min and calcine it at a constant temperature for 4 hours to obtain the catalyst carrier.
[0045] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0046] Step five, the prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, followed by a second impregnation of equal volume for 1 hour, dried at 120°C under a nitrogen atmosphere for 2 hours, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain product 4.
[0047] Example 5
[0048] Step 1: first, place 600g of pseudo-boehmite, 24g of sesbania powder, and 36g of hydroxymethyl cellulose in a kneader and stir and mix for 10 minutes. Take 270ml of deionized water and 270ml of nitric acid to prepare a solution, adjust the pH value to 4, then add the prepared solution to the kneader, knead until the product is a lump-like material, and adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0049] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours.
[0050] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 75°C for 4 hours under a nitrogen atmosphere, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 8 hours to obtain the catalyst carrier.
[0051] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0052] Step 5, the prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, followed by a second impregnation of an equal volume for 1 hour, dried at 100°C for 2 hours under a nitrogen atmosphere, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain product 5.
[0053] Comparative Example 1
[0054] Step 1: first, put 600g pseudo-boehmite, 24g sesbania powder, and 36g hydroxymethyl cellulose in a kneader and stir for 10 minutes. Add 270ml of deionized water into the kneader and knead until the product is a mass-like material, and adjust the amount of water added to the product to a suitable dryness and wetness.
[0055] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 6 hours.
[0056] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 75°C for 4 hours, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 8 hours to obtain the catalyst carrier.
[0057] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0058] Step 5: The prepared impregnation liquid is mixed with the catalyst support obtained above in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain Comparative Material 1.
[0059] Comparative Example 2
[0060] Step 1: weigh 200 g of pseudo-boehmite powder and 8 g of sesbania powder, add 90 mL of ammonium bicarbonate solution, mix and stir evenly to obtain a material. Adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0061] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 6 hours.
[0062] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 100°C for 4 hours, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 8 hours to obtain the catalyst carrier.
[0063] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0064] Step 5: The prepared impregnation liquid is mixed with the above-obtained catalyst support in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain Comparative Material 2.
[0065] Comparative Example 3
[0066] Step 1: weigh 200 g of pseudo-boehmite powder and 8 g of sesbania powder, add 90 mL of ammonium bicarbonate solution, mix and stir evenly to obtain a material. Adjust the amount of water added to the product until the dryness and humidity are appropriate.
[0067] Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 12 hours.
[0068] Step three, transfer the clover-shaped catalyst carrier after standing to a muffle furnace, dry it at 100°C for 4 hours, and then heat it to 500°C at a rate of 3°C / min and calcine it at a constant temperature for 8 hours to obtain the catalyst carrier.
[0069] Step 4: Add deionized water to 94.578 g of ammonium molybdate and 43.224 g of nickel nitrate to fully dissolve them to prepare a stable impregnation solution.
[0070] Step 5: The prepared impregnation liquid is mixed with the above-obtained catalyst support in a fixed ratio and impregnated for 2 hours, then dried at 50°C for 4 hours, and then heated to 500°C at a rate of 3°C / min and calcined at a constant temperature for 4 hours to obtain Comparative Material 2.
[0071] The physical properties of the products obtained in Examples 1 to 5 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 1.
[0072] Table 1
[0073]
[0074] The denitrification and desulfurization performance of the catalysts obtained in Examples 1 to 5 and Comparative Examples 1 to 3 was evaluated using Middle East residual oil. The results are shown in Table 2.
[0075] Table 2
[0076] Serial number HDN % HDS% Example 1 85.3 81.7 Example 2 82.4 82.5 Example 3 86.5 86.2 Example 4 81.2 82.9 Example 5 83.8 85.4 Comparative Example 1 73.3 72.5 Comparative Example 2 62.7 63.8 Comparative Example 3 60.5 61.2
[0077] The present invention obtains a new hydrodenitrification and desulfurization catalyst by redesigning the product raw materials and the preparation process of the catalyst. The maximum denitrification rate of the catalyst can reach 86.5%, the maximum desulfurization rate can reach 86.2%, and the finished product density of the catalyst product is controlled at 0.60-0.80 g / cm 3 , pore volume greater than 0.3 ml / g, specific surface area greater than 130 cm 3 / g, the service life of the product is increased to 2-3 years, which can effectively reduce the amount of hydrodenitrogenation and desulfurization catalyst used, reduce the cost of using hydrodenitrogenation and desulfurization catalysts, and improve the hydrodenitrogenation and desulfurization effect of the reactor.
[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A catalyst for deep hydrodenitrogenation and desulfurization and a preparation method thereof, wherein the raw material used is a pseudo-boehmite product, and the active components contain molybdenum oxide, nickel oxide and silicon oxide.
2. The deep hydrodenitrogenation and desulfurization catalyst according to claim 1, characterized in that: The active component molybdenum oxide in the catalyst is 18-25%.
3. The deep hydrodenitrogenation and desulfurization catalyst according to claim 1, characterized in that: The active component nickel oxide in the catalyst is 3.3-5.5%.
4. The deep hydrodenitrogenation and desulfurization catalyst according to claim 1, characterized in that: The active component silicon oxide in the catalyst is 1 to 3%.
5. The deep hydrodenitrogenation and desulfurization catalyst according to claim 1, characterized in that: Catalyst product specific surface area 130~170m 2 / g, pore volume 0.3~0.5ml / g, pore diameter 7~12nm.
6. The deep hydrodenitrogenation and desulfurization catalyst according to claim 1, characterized in that: The raw material pseudo-boehmite has a specific surface area of 280-350m 2 / g, and the pore volume is 0.8~1.2ml / g.
7. The pseudo-boehmite according to claim 6, characterized in that: The raw material pseudo-boehmite is added with anti-coking factor silicon element, the content of which is 2% to 4%.
8. A catalyst for deep hydrodenitrogenation and desulfurization according to claim 1 and a method for preparing the same, characterized in that ; Step 1: Place pseudo-boehmite, sesbania powder and hydroxymethyl cellulose in a kneader and stir for 10 to 30 minutes. Then, take deionized water and inorganic acid to prepare a solution, adjust the pH value to 2 to 4, add the prepared solution to the kneader, knead until the product is a mass-like material, and adjust the amount of water added to the product until the dryness and wetness are appropriate; Step 2: transfer the prepared agglomerated material to an extruder, select a 2.0 mm clover-shaped module, extrude it into a clover-shaped catalyst carrier, and then let the extruded clover-shaped catalyst carrier stand for 24 hours; Step 3, transferring the clover-shaped catalyst carrier after standing to a muffle furnace, drying it at 50-100° C. for 4 hours under a nitrogen atmosphere, and then heating it to 500-650° C. at a rate of 3° C. / min and calcining it at a constant temperature for 4-8 hours to obtain the catalyst carrier; Step 4, adding deionized water to the soluble molybdenum salt and nickel salt to fully dissolve them to prepare a stable impregnation solution; Step 5: Mix the prepared impregnation liquid with the catalyst carrier obtained above in a fixed ratio and impregnate for 2 hours, then dry it at 50-100°C for 4 hours in a nitrogen atmosphere, then perform a second impregnation of equal volume for 1 hour, dry it at 75-120°C for 2 hours in a nitrogen atmosphere, and then heat it to 300-500°C at a rate of 3°C / min and calcine it at a constant temperature for 4 hours to obtain the catalyst product.
Citation Information
Patent Citations
Preparation method for novel heavy oil hydrogenization demetallization catalyst adopting macroporous structures
CN103657667A
Preparation method of high active site density hydrotreating catalyst
CN104248965A
Hydrodechlorination catalyst, preparation method and application thereof
CN104815681A
Preparation method of environment-friendly heavy oil hydrofining catalyst
CN110479333A
Preparation method of low-density protection catalyst suitable for coal tar hydrogenation
CN113731434A
Cited By
High-activity anti-coking difunctional hydrocracking catalyst and preparation method thereof
CN122076417A
Highly active anti-coking bifunctional hydrocracking catalyst and its preparation method
CN122076417B